2020
DOI: 10.2196/17293
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administered Skills-Based Virtual Reality Intervention for Chronic Pain: Randomized Controlled Pilot Study

Abstract: Background Patients with chronic pain often have limited access to comprehensive care that includes behavioral pain management strategies. Virtual reality (VR) is an immersive technology and emerging digital behavioral pain therapy with analgesic efficacy for acute pain. We found no scientific literature on skills-based VR behavioral programs for chronic pain populations. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 381 publications
(483 reference statements)
1
87
0
2
Order By: Relevance
“…Virtual reality (VR) is a newly emerging and promising intervention tool for chronic pain treatment to both distract individuals from their pain and facilitate otherwise painful or feared movements [1,2]. For adults exhibiting a variety of chronic pain conditions-including spine, shoulder, abdominal, hip, musculoskeletal, and neuropathic pain-research has demonstrated the efficacy of VR tools, finding significant reductions in subjective reports of pain both during and after VR sessions [3][4][5][6][7]. VR treatments have also been shown to significantly reduce pain, prompt physiological reactions of relaxation, improve physical functioning, and improve social role functioning for adults with chronic low back pain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR) is a newly emerging and promising intervention tool for chronic pain treatment to both distract individuals from their pain and facilitate otherwise painful or feared movements [1,2]. For adults exhibiting a variety of chronic pain conditions-including spine, shoulder, abdominal, hip, musculoskeletal, and neuropathic pain-research has demonstrated the efficacy of VR tools, finding significant reductions in subjective reports of pain both during and after VR sessions [3][4][5][6][7]. VR treatments have also been shown to significantly reduce pain, prompt physiological reactions of relaxation, improve physical functioning, and improve social role functioning for adults with chronic low back pain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…В указанном аспекте сам факт наличия болевых ощущений значим для тяжести депрессивных настроений и выраженности тревоги и беспокойства [36], что ухудшает результаты медикаментозной терапии, приверженность к лечению, доверие к лечащему врачу. Применение виртуальных методов воздействия по ме-Южно-Российский журнал терапевтической практики South Russian Journal of Therapeutic Practice 2021;2(1):83-89 тодике вовлечённой отвлечённости позволяет реализовывать три различных механизма: отвлечение, нейромодуляцию и терапию с постепенным воздействием, -что в настоящее время рассматривается как возможная комплементарная немедикаментозная терапия различных болевых синдромов [37,38]. В нашем исследовании также подтверждена дополнительная анальгетическая возможность использования виртуальных воздействий с применением VR-технологий в лечении больных с ревматоидным артритом.…”
Section: Discussionunclassified
“…Such skills may be acquired and rehearsed in interactive VR scenarios, and made effective through the implementation of gamification, task progression, feedback and reward schemes. One example of a simple implementation of skills training in VR for chronic pain is relaxation training for stress management (Darnall et al, 2020). Here, training to self-induce a relaxed state can be made easier by overlaying relaxing audio-visual contexts and breath detection and feedback techniques (Darnall et al, 2020).…”
Section: Self-efficacy: Improving Actual Controlmentioning
confidence: 99%
“…One example of a simple implementation of skills training in VR for chronic pain is relaxation training for stress management (Darnall et al, 2020). Here, training to self-induce a relaxed state can be made easier by overlaying relaxing audio-visual contexts and breath detection and feedback techniques (Darnall et al, 2020). Notably, such interventions may have implications beyond improving perceived capacity to manage stress.…”
Section: Self-efficacy: Improving Actual Controlmentioning
confidence: 99%
See 1 more Smart Citation